2011
DOI: 10.1021/jm2001025
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Docking, and Biological Evaluation of Novel Diazide-Containing Isoxazole- and Pyrazole-Based Histone Deacetylase Probes

Abstract: The design, synthesis, docking, and biological evaluation of novel potent HDAC3 and HDAC8 isoxazole- and pyrazole-based diazide probes suitable for Binding Ensemble Profiling with Photoaffinity Labeling (BEProFL) experiments in cells is described. Both the isoxazole- and pyrazole-based probes exhibit low nanomolar inhibitory activity against HDAC3 and HDAC8, respectively. The pyrazole-based probe 3f appears to be one of the most active HDAC8 inhibitors reported in the literature with an IC50 of 17 nM. Our dock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
72
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 29 publications
1
72
0
Order By: Relevance
“…Previous studies have reported that the diazide-containing isoxazoles were used to target histone deacetylases. 46 Additionally, 3-substituted-1,2-isoxazole was reported to show potent inhibitory activity against HDAC6. 47 On the other hand, the second deacetylase domain of HDAC6 possesses tubulin deacetylase activity, 48 therefore, we focussed on this domain.…”
Section: 6mentioning
confidence: 99%
“…Previous studies have reported that the diazide-containing isoxazoles were used to target histone deacetylases. 46 Additionally, 3-substituted-1,2-isoxazole was reported to show potent inhibitory activity against HDAC6. 47 On the other hand, the second deacetylase domain of HDAC6 possesses tubulin deacetylase activity, 48 therefore, we focussed on this domain.…”
Section: 6mentioning
confidence: 99%
“…4; Table 1) [80]. For instance, Neelarapu et al used a diazide probe for mapping the surface binding groups of class I HDAC isoforms.…”
Section: Surface Group Modificationsmentioning
confidence: 99%
“…This compound also inhibited other class I and II HDACs at nM concentrations (Table 1). However, removing the diazide group (9) resulted in reduced selectivity against all HDACs, suggesting the importance of the two azide moieties for HDAC8 selectivity [80]. There are some reported compounds (10)(11)(12)(13) in which modifications to the cap region resulted in class selectivity (Fig.…”
Section: Surface Group Modificationsmentioning
confidence: 99%
“…28 Synthetic procedures and data for compounds 1a , 1b , 1e and 8 and 2a , 2b , 3a , 3b and 10 were previously reported by us. 19, 29 [4-(Azidomethyl)phenyl]methanol and 2-azidoethanol were synthesized according to the reported methods. 30, 31 …”
mentioning
confidence: 99%
“…19, 29 The resulting IC 50 values are given in Table 1. The analysis of the SAR was facilitated by docking of the ligands to HDAC8 (PDB:1T64) 27 using GOLD v.5.1.…”
mentioning
confidence: 99%